Phytochemical screening and larvicidal activity of murraya koenigii leaves ethanolic extract against aedes aegypti - Ramli, Norazsida; Mohd Roslin, Nur Elia Amira; Darnis, Deny Susanti (IIUM Press, International Islamic University Malaysia, 2018)
World Health Organization (WHO) estimated over 100 million dengue infections to happen annually worldwide involving more than 2.5 billion people. Temephos or abate is a larvicide that has been used in vector control to eradicate mosquito larvae. Though practically low risk, there had been resistance problem reported with continuous use. This study seeks to find an effective and safer alternative to abate by assessing the use of ethanolic extract of Murraya koenigii leaves as larvicidal agent against Aedes aegypti. M.koenigii leaves were macerated for 3 days with absolute ethanol and evaporated using rotary vapor to produce the crude extract. The crude extract was subjected to phytochemical screening using standard qualitative method. For bioassay, the crude extract underwent a serial dilution to produce 3 concentrations of 100 ppm (C1), 50 ppm (C2) and 10 ppm (C3) with abate and absolute ethanol as negative and positive control respectively. Bioassay for larvicidal effect was conducted in accordance to WHO standard method. Phytochemical screening of ethanolic extract of M. koenigii leaves revealed the presence of alkaloid, steroid and saponin. The bioassay shows that after 24 hours, the mortality rate of C1, C2 and C3 larvae were 100%, 38% and 0% and when further extended to 48 hours, the rate increased to 100% and 46% for C2 and C3 respectively. The LC50 and LC99 post 24 hours were 54.489 ppm and 93.961 ppm respectively whilst at post 48 hours, the LC50 and LC99 were 10.263 ppm and 16.176 ppm respectively. The results show that up to 48 hours duration of exposure, the mortality rate increase whilst the lethal concentration (LC50 and LC99) decreases. Upon examination on larvae deformities at post 24 and 48 hours, all test concentrations and negative control exhibit normal morphology. Positive control, however, exhibit deformities characterized by twisted and fragmented insides. When statistically analyzed, C1 larvicidal activity was proven comparable with abate at 24 hours while C2 needed 48 hours exposure to be on par. Based on the results, it could be argued that the ethanolic extract of M.koenigii leaves does hold promising value to be further developed as larvicidal.